33 Cetuximab paying toll to improve its therapeutic efficacy – Improving cetuximab-mediated head and neck cancer treatment via co-activation of Fc-receptors and toll-like receptors. Issue 5 (May 2015) - Bakema, J.; Ganzevles, S.; Tuk, K.; van Egmond, M.; Leemans, C.R.; Braakhuis, B.J.M.; Brakenhoff, R.H.
<x xml:space="preserve">Abstract</x> Background Cetuximab, a therapeutic antibody used to treat Head and Neck Squamous Cell Carcinoma (HNSCC), blocks binding of epidermal growth factor to its receptor (EGFR) on tumor cells, thereby inhibiting tumor outgrowth. However, antibodies can also activate anti-tumor immune responses through binding of Fcgamma-receptors (FcgRs) on effector cells. In this way, immune effector cells bind to tumor cells, become activated and execute their tumoricidal functions. NK cells, for instance, can eliminate tumors via release of toxic components whereas macrophages phagocytose and kill tumor cells intracellularly. The immune suppressive tumor microenvironment severely hampers the efficacy of therapeutic antibodies like cetuximab to induce adequate anti-tumor responses via patients' own immune cells. We recently demonstrated that simultaneous activation of FcgRs and pathogen recognizing Toll-like receptors (TLRs) on immune cells induces strong and profound inflammatory responses. Therefore, our aim is to investigate whether co-activation of TLRs during cetuximab treatment overrules the immune suppressive environment inflicted by the tumor. Material and methods We performed cytotoxicity assays with HNSCC patient-derived tumor cell lines and cetuximab with or without Toll-like receptor co-activation. We tested these treatments with several types of effector immune cells. Furthermore, we investigated changes in cytokine profiles of HNSCC cell lines treated with immune effector cells and cetuximab with or without Toll-like receptor co-activation. Results We now demonstrate that cetuximab in combination with Toll-like receptor co-activation improves tumoricidal functions of immune effector cells. Furthermore, we demonstrate that this improved capacity to eliminate tumor cells is linked with induction of a pro-inflammatory cytokine profile. Conclusion Based on our results we anticipate that cetuximab treatment in combination with Toll-like receptor co-activation will overcome the tumor immunosuppressive environment of HNSCC and thus positively affects tumor killing capacity of immune effector cells. This novel strategy may improve current cetuximab treatment of patients with HNSCC.